Incorporation of tumor motion directionality in margin recipe: The directional MidP strategy. (November 2021) - Vander Veken, Loïc; Dechambre, David; Sterpin, Edmond; Souris, Kevin; Van Ooteghem, Geneviève; Aldo Lee, John; Geets, Xavier
Graphical abstract: Highlights: Directional MidP method incorporates motion directionality in PTV definition. Higher 4D D95% and D99% are achieved with the proposed method. PTV volume is similar compared to classical MidP strategy. Abstract: Purpose: Planning target volume (PTV) definition based on Mid-Position (Mid-P) strategy typically integrates breathing motion from tumor positions variances along the conventional axes of the DICOM coordinate system. Tumor motion directionality is thus neglected even though it is one of its stable characteristics in time. We therefore propose the directional MidP approach (MidP dir), which allows motion directionality to be incorporated into PTV margins. A second objective consists in assessing the ability of the proposed method to better take care of respiratory motion uncertainty. Methods: 11 lung tumors from 10 patients with supra-centimetric motion were included. PTV were generated according to the MidP and MidP dir strategies starting from planning 4D CT. Results: PTVMidP dir volume didn't differ from the PTVMidP volume: 31351 mm 3 IC95% [17242–45459] vs. 31003 mm 3 IC95% [ 17347–44659], p = 0.477 respectively. PTVMidP dir morphology was different and appeared more oblong along the main motion axis. The relative difference between 3D and 4D doses was on average 1.09%, p = 0.011 and 0.74%, p = 0.032 improved with directional MidP for D99% and D95% . D2% was not significantly different between both approaches. The improvement in dosimetric coverage fluctuated substantially from one lesion to another and was all the more important as motion showed a large amplitude, some obliquity with respect to conventional axes and small hysteresis. Conclusions: Directional MidP method allows tumor motion to be taken into account more tightly as a geometrical uncertainty without increasing the irradiation volume.